UPAYA DETEKSI MANDIRI TANDA BAHAYA KEHAMILAN DENGAN PREEKLAMSIA MENGGUNAKAN SPELLING PUZZLE GAME - Mahundingan, Rosari Oktaviana; Andriani, Dewi; Kurniawan, Afif; Tjokro, Silvia Haniwijaya (PPM STIKES Adi Husada, 2024)
Preeclampsia is a condition identified as diastolic blood pressure ≥ 90 mmHg at ≥ 20 weeks of gestation. Preeclampsia is a risky condition for pregnant women, is one of the causes of maternal death in Indonesia, and causes fetal growth to be hampered. Games that can help you understand more easily are puzzles, containing word games. One of the puzzle games is the Spelling Puzzle Game. This activity aims to independently detect preeclampsia in pregnant women using the Spelling Puzzle Game. The method used in community service is health education outreach using the Spelling Puzzle Game media. The targets for this activity were pregnant women, women of childbearing age (WUS), and cadres in the RW 07 Kapasan Village area, Simokerto District, totaling 21 respondents. The results of the activity showed that the level of knowledge about preeclampsia was in the good category of 100% (21 respondents). Respondents should be able to carry out early detection of preeclampsia independently to help reduce or control blood pressure